Augustine and the Functions of Concupiscence. - Nisula, Timo. (Vigiliae Christianae, Supplements, 2012)
Augustine's ideas of sinful desire, including its sexual manifestations, have fueled controversies for centuries. In Augustine and the Functions of Concupiscence , Timo Nisula analyses Augustine's own theological and philosophical concerns in his extensive writings about evil desire ( concupiscentia, cupiditas, libido ). Beginning with a terminological survey of the vocabulary of desire, the book demonstrates how the concept of evil desire was tightly linked with Augustine's fundamental theological views of divine justice, the origin of evil, Christian virtues and grace. This book offers a comprehensive account of Augustine's developing views of concupiscence and provides an innovative, in-depth picture of the theological imagination behind disputed ideas of sex, temptation and moral responsibility.